Provision of Road Signs as an Effort to Clarify the Location of Population Data in Sanja Village - Alfajri, Nadia; Rinda, Rachmatullaily Tinakartika (Jurnal Pengabdian Nusantara, 2024)
This study aims to educate the importance of providing road signs as an effort to clarify the location of population data, this activity was carried out in Sanja Village, RT 04 RW 02, Citeureup District, Bogor Regency, using descriptive qualitative methods. The results of this study are that the road signboard becomes a barrier between one road and another and immigrants and local residents are easy to find addresses.